An analysis of emerging trends and transformations in global healthcare. Issue 2 (13th May 2019) - Yeganeh, Hamid
Abstract : Purpose: The purpose of this paper is to analyze the main global transformations of the healthcare sector and their underlying causes and effects. Design/methodology/approach: The study focuses on several important trends including the increasing life expectancy and aging, the rise of non-communicable diseases, the risks of pandemics, medication expenditure, the globalization of healthcare and technological innovations such as digitization, robotic and nanomedicine. Findings: The analysis indicates that the world populations will be much older in the near future and the healthcare sector will witness significant growth opportunities. The aging populations will put more pressure on healthcare systems and increase the incidence of non-communicable diseases. In a globalized world, the risks of global pandemics are expected to increase. The surge in the medication expenditure will put much pressure on healthcare systems, insurers, patients, employers and providers. The healthcare sector is characterized by its above-average growth in the USA and much of the developed world. Therefore, the share of healthcare in gross domestic product will continue to rise. The digitization and globalization of healthcare may involve major disruptions in the location and the type of care. New materials particularly nanoparticles will be used to enhance the precision, quality and efficacy of diagnostics, medications and treatments. Originality/value: The paper touches on several areas including demographic, clinical, financial, managerial and technological transformations and examines their implications for the healthcare sector.